The understanding by design guide to creating high-quality units - Wiggins, Grant P., 1950- (ASCD, 2011)
This book introduces version 2.0 of the Understanding by Design template and allows readers to download fillable electronic forms to help incorporate standards, advance their understanding of backward design, and improve student learning.